Pengaruh Disiplin Kerja dan Komitmen Organisasi terhadap Kinerja Guru di Kabupaten Banyuwangi dengan Kepuasan Kerja sebagai Variabel Intervening - Tasya Dian Ayu Pramesti (Fakultas Ekonomi dan Bisnis, 2026)
This study was conducted to identify the effect of Work Discipline and Organizational Commitment on Teacher Performance in Banyuwangi Regency with Job Satisfaction as an Intervening Variable. The research design is quantitative-based using explanatory research methods. Path analysis is used to test the model of causal relationships between variables. The research variables are Work Discipline, Organizational Commitment, Job Satisfaction, and Teacher Performance. The population in this study consists of civil servant teachers (PNS) at SMAN 1 Pesanggaran and SMAN 1 Bangorejo. The sample in this study includes all civil servant teachers, totaling 45 respondents. Data was collected primarily using questionnaires. Based on the discussion, the research results are: 1) Work Discipline has a significant effect on Job Satisfaction; 2) Organizational Commitment has a significant effect on Job Satisfaction; 3) Work Discipline has an insignificant effect on Teacher Performance. 4) Organizational Commitment has an insignificant effect on Teacher Performance; 5) Job Satisfaction has a significant effect on Performance; 6) Work Discipline has a significant effect on Performance through Job Satisfaction; 7) Organizational Commitment has a significant effect on Performance through Job Satisfaction.
Validasi dan Finalisasi Ratna 8 Juli 2026
Keywords: Work Discipline; Organizational Commitment; Job Satisfaction; Teacher Performance